Evaluation of DoS attacks on Commercial Wi-Fi-Based UAVs - Vasconcelos, Gabriel; Miani, Rodrigo; Guizlini, Vitor; Souza, Jefferson (International Journal of Communication Networks and Information Security (IJCNIS), 2022)
One of the biggest challenges for the use of Unmanned Aerial Vehicles (UAVs) in large-scale real-world applications is security. However, most of research projects related to robotics does not discuss security issues, moving on directly to studying classical problems (i.e., perception, control, planning). This paper evaluates the effects of availability issues (Denial of Service attacks) in two commonly used commercially available UAVs (AR.Drone 2.0 and 3DR SOLO). Denial of Service (DoS) attacks are made while the vehicles are navigating, simulating common conditions found both by the general public and in a research scenario. Experiments show how effective such attacks are and demonstrate actual security breaches that create specific vulnerabilities. The results indicate that both studied UAVs are susceptible to several types of DoS attacks which can critically influence the performance of UAVs during navigation, including a decrease in camera functionality, drops in telemetry feedback and lack of response to remote control commands. We also present a tool that can be used as a failsafe mechanism to alert the user when a drone is reaching out a determined flight limit range, avoiding availability issues.